Non-lytic egression of infectious bursal disease virus (IBDV) particles from infected cells - Méndez, Fernando (2017)
nfectious bursal disease virus (IBDV), a member of the Birnaviridae family, is responsible for a devastating immunosuppressive disease affecting juvenile domestic chickens. IBDV particles are naked icosahedrons enclosing a bipartite double-stranded RNA genome harboring three open reading frames (ORF). One of these ORFs codes for VP5, a non-structural polypeptide dispensable for virus replication in tissue culture but essential for IBDV pathogenesis. Using two previously described recombinant viruses, whose genomes differ in a single nucleotide, expressing or not the VP5 polypeptide, we have analyzed the role of this polypeptide during the IBDV replication process. Here, we show that VP5 is not involved in house-keeping steps of the virus replication cycle; i.e. genome transcription/replication, protein translation and virus assembly. Although infection with the VP5 expressing and non-expressing viruses rendered similar intracellular infective progeny yields, striking differences were detected on the ability of their progenies to exiting infected cells. Experimental data shows that the bulk of the VP5-expressing virus progeny efficiently egresses infected cells during the early phase of the infection, when viral metabolism is peaking and virus-induced cell death rates are as yet minimal, as determined by qPCR, radioactive protein labeling and quantitative real-time cell death analyses. In contrast, the release of the VP5-deficient virus progeny is significantly abridged and associated to cell death. Taken together, data presented in this report show that IBDV uses a previously undescribed VP5-dependent non-lytic egress mechanism significantly enhancing the virus dissemination speed. Ultrastructural analyses revealed that newly assembled IBDV virions associate to a vesicular network apparently facilitating their trafficking from virus assembly factories to the extracellular milieu, and that this association requires the expression of the VP5 polypeptide.